Topographical factors related to flooding frequency promote ecosystem multifunctionality of riparian floodplains. (December 2021) - Sendek, Agnieszka; Kretz, Lena; van der Plas, Fons; Seele-Dilbat, Carolin; Schulz-Zunkel, Christiane; Vieweg, Michael; Bondar-Kunze, Elisabeth; Weigelt, Alexandra; Wirth, Christian
Highlights: We described floodplain functioning with the ecosystem multifunctionality index. Both negative and positive correlation occurred between floodplain functions. Multifunctionality declines with distance to the water table and hydrological distance. Effect of distance to the water table is stronger than of hydrological distance. Multifunctionality indices link floodplain functioning with flooding. Abstract: Various ecosystem functions provided by floodplains depend on a natural river activity and floodplain morphology. Therefore, anthropogenic alterations of rivers modify their flooding regimes and may affect the provisioning of numerous ecosystem functions. Restoration projects, which aim at reestablishing natural processes of floodplains, require a better understanding of the ecosystem's ability to simultaneously provide multiple functions (multifunctionality) and how this relates to the environmental template. Here we investigate the relationship between environmental drivers and ecosystem multifunctionality. We focus on 24 ecosystem functions, representing five ecosystem services provided by floodplains of the Mulde River: plant productivity, biodiversity provisioning, retention of sediments, nutrients and pollutants. These functions were measured on 74 plots located on three well preserved floodplain sites of the Mulde River. We described synergies and trade-offs between single functions using correlations and calculated quantitative measures of ecosystem multifunctionality, quantified as the number of functions provided above either 50% of maximal functioning, or 75% of maximal functioning. We then explored relations of multifunctionality with two environmental factors, which also affect the probability of flooding i.e., the hydrological distance and the distance to the water table. Although numerous functions related to sedimentation processes were positively correlated to each other, they traded off with functions related to biodiversity provisioning. This advocates the application of a holistic measure of ecosystem functioning. Multifunctionality indices decreased with an increase of both distance to the water table and hydrological distance, with effects of the distance to the water table being most strongly negative. These findings imply that ecosystem multifunctionality is highest at sites which are flooded regularly. We conclude that restoration attempts which shorten hydrological distance and distance to the water table, like removal of artificial embankments or reconstruction of side channels, may have a positive effect not only on single functions, but also on overall ecosystem multifunctionality. We also advocate the application of a multifunctionality measure to facilitate management and restoration of floodplains.